Nasal Epithelial Barrier Integrity and Tight Junctions Disruption in Allergic Rhinitis: Overview and Pathogenic Insights - Nur Husna, Siti Muhamad; Tan, Hern-Tze Tina; Md Shukri, Norasnieda; Mohd Ashari, Noor Suryani; Wong, Kah Keng (Frontiers in Immunology, 2021)
Allergic rhinitis (AR) is a common disorder affecting up to 40% of the population worldwide and it usually persists throughout life. Nasal epithelial barrier constitutes the first line of defense against invasion of harmful pathogens or aeroallergens. Cell junctions comprising of tight junctions (TJs), adherens junctions, desmosomes and hemidesmosomes form the nasal epithelial barrier. Impairment of TJ molecules plays causative roles in the pathogenesis of AR. In this review, we describe and discuss the components of TJs and their disruption leading to development of AR, as well as regulation of TJs expression by epigenetic changes, neuroimmune interaction, epithelial-derived cytokines (thymic stromal lymphopoietin, IL-25 and IL-33), T helper 2 (Th2) cytokines (IL-4, IL-5, IL-6 and IL-13) and innate lymphoid cells. These growing evidence support the development of novel therapeutic approaches to restore nasal epithelial TJs expression in AR patients.